Đình Phong Nguyễn

hoàn thành trước 6H sáng ngày mai

1: 

a: \(A=3\dfrac{1}{10}:\left[4\cdot\left(-3\right)^2-2^3:\dfrac{8}{5}\right]\)

\(=3,1:\left[4\cdot9-8\cdot\dfrac{5}{8}\right]\)

\(=3,1:\left(36-5\right)=3,1:31=0,1\)

b: \(B=\left(1\dfrac{1}{3}\right)\left(1\dfrac{1}{8}\right)\left(1\dfrac{1}{15}\right)\cdot...\cdot\left(1\dfrac{1}{99}\right)\)

\(=\dfrac{4}{3}\cdot\dfrac{9}{8}\cdot\dfrac{16}{15}\cdot...\cdot\dfrac{100}{99}\)

\(=\dfrac{2\cdot2}{1\cdot3}\cdot\dfrac{3\cdot3}{2\cdot4}\cdot\dfrac{4\cdot4}{3\cdot5}\cdot...\cdot\dfrac{10\cdot10}{9\cdot11}\)

\(=\dfrac{2\cdot3\cdot4\cdot...\cdot10}{1\cdot2\cdot3\cdot...\cdot9}\cdot\dfrac{2\cdot3\cdot...\cdot10}{3\cdot4\cdot5\cdot...\cdot11}\)

\(=\dfrac{10}{1}\cdot\dfrac{2}{11}=\dfrac{20}{11}\)

2: \(C=\dfrac{5}{2\cdot7}+\dfrac{16}{7\cdot9}-\dfrac{2}{9\cdot11}-\dfrac{29}{11\cdot18}\)

\(=\dfrac{1}{2}-\dfrac{1}{7}+\dfrac{1}{7}+\dfrac{1}{9}-\left(\dfrac{1}{9}-\dfrac{1}{11}\right)-\dfrac{1}{11}-\dfrac{1}{18}\)

\(=\dfrac{1}{2}+\dfrac{1}{9}-\dfrac{1}{9}+\dfrac{1}{11}-\dfrac{1}{11}-\dfrac{1}{18}=\dfrac{1}{2}-\dfrac{1}{18}\)

\(=\dfrac{8}{18}=\dfrac{4}{9}\)

Bình luận (0)

Các câu hỏi tương tự
Ng Gia Hân
Xem chi tiết
Ng Gia Hân
Xem chi tiết
M r . V ô D a n h
Xem chi tiết
longkkk
Xem chi tiết
Vũ Minh Phú
Xem chi tiết
Vũ Minh Phú
Xem chi tiết
Vũ Minh Phú
Xem chi tiết
Vũ Minh Phú
Xem chi tiết
Jenny phạm
Xem chi tiết
Jenny phạm
Xem chi tiết